Isothermal Cyclic Conversion of Methane into Methanol over Copper‐Exchanged Zeolite at Low Temperature. Issue 18 (24th March 2016) - Tomkins, Patrick; Mansouri, Ali; Bozbag, Selmi E.; Krumeich, Frank; Park, Min Bum; Alayon, Evalyn Mae C.; Ranocchiari, Marco; van Bokhoven, Jeroen A.
Abstract: Direct partial oxidation of methane into methanol is a cornerstone of catalysis. The stepped conversion of methane into methanol currently involves activation at high temperature and reaction with methane at decreased temperature, which limits applicability of the technique. The first implementation of copper‐containing zeolites in the production of methanol directly from methane is reported, using molecular oxygen under isothermal conditions at 200 °C. Copper‐exchanged zeolite is activated with oxygen, reacts with methane, and is subsequently extracted with steam in a repeated cyclic process. Methanol yield increases with methane pressure, enabling reactivity with less reactive oxidized copper species. It is possible to produce methanol over catalysts that were inactive in prior state of the art systems. Characterization of the activated catalyst at low temperature revealed that the active sites are small clusters of copper, and not necessarily di‐ or tricopper sites, indicating that catalysts can be designed with greater flexibility than formerly proposed. Abstract : Under pressure : Direct, stepped oxidation of methane into methanol was realized in an isothermal reaction. Otherwise inactive copper clusters were activated by employing higher methane pressures. This method provides new material design and process development opportunities that enable direct conversion of methane into methanol.